Must love flowers : a novel [compact disc, unabridged] - Macomber, Debbie (Random House Audio, 2023)
Joan Sample is not living the life she thought she would. Now a widow and an empty nester, Joan is content being something of a recluse. But after another birthday spent alone, she is finally inclined to listen to her sister, who has been begging Joan to get back out into the world. With her encouragement, Joan makes big strides, taking care of her overgrown lawn, making new friends through a grief support group, and even renting out a room to a local college student. Before long Joan is finally starting to feel like herself again. Across town, Maggie Herbert works mornings as a barista, tending to rushed and annoyed customers before taking afternoon classes to become a nurse practitioner. She's been living with her alcoholic father, avoiding his temper and struggling to pay the bills. But she begins to envision a new future when she finds a room for rent at a reasonable price, with a landlady who seems nice enough. Only after she moves in does she realize that her least favorite customer happens to be Joan's son, and she's just taken his childhood room. Despite a rocky start, Maggie begins to see a different side to the grumpy customer who was once her nemesis. At the same time, Joan grows closer with the landscaper who's revitalizing her lawn. And as they confront the trials of life, new love, and family, the two women offer each other the support they had been missing. But will the risks they take be worth it in the end?